PECULIARITIES OF THE INDIVIDUAL ORGANIZATION STUDENTS 'WORKS IN MATHEMATICS LESSONS IN CONTEXTS PERSONALLY FOCUSED LEARNING (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the possibilities of organizing individual work of pupils at the lessons of mathematics and the conditions o f this work effectiveness.